2023
DOI: 10.3390/jmse11081509
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning-Based Fault Warning Model for Exhaust Temperature Prediction and Fault Warning of Marine Diesel Engine

Zhenguo Ji,
Huibing Gan,
Ben Liu

Abstract: Marine diesel engines are essential for safe navigation. By predicting the operating conditions of diesel engines, the performance of marine diesel engines can be improved, failures can be prevented to reduce maintenance costs, and emissions can be controlled to protect the environment. To this end, this paper proposes a hybrid neural network (HNN) prediction model (CNN-BiLSTM-Attention) based on deep learning (DL) for predicting the exhaust gas temperature (EGT) of marine diesel engines. CNN is used to extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…New technology with intelligence was also used in the health management of USVs, exemplified by a hybrid neural network (HNN) prediction model, which integrates Convolutional Neural Networks (CNN), Bidirectional Long Short-Term Memory (BiLSTM) and Attention mechanisms, designed specifically for the prediction of Exhaust Gas Temperature (EGT) in marine diesel engines. This approach provides a new way of thinking for the research of fault early warning and the health management of marine diesel engines [74]. To speed up autonomy, the Unmanned Maritime Systems Program Office (PMS 406) is enhancing autonomy in unmanned maritime vehicles through the Unmanned Maritime Autonomy Architecture (UMAA) for software standards and the Rapid Autonomy Integration Lab (RAIL) for developing new capabilities [75].…”
Section: Enhanced Intelligence and Autonomymentioning
confidence: 99%
“…New technology with intelligence was also used in the health management of USVs, exemplified by a hybrid neural network (HNN) prediction model, which integrates Convolutional Neural Networks (CNN), Bidirectional Long Short-Term Memory (BiLSTM) and Attention mechanisms, designed specifically for the prediction of Exhaust Gas Temperature (EGT) in marine diesel engines. This approach provides a new way of thinking for the research of fault early warning and the health management of marine diesel engines [74]. To speed up autonomy, the Unmanned Maritime Systems Program Office (PMS 406) is enhancing autonomy in unmanned maritime vehicles through the Unmanned Maritime Autonomy Architecture (UMAA) for software standards and the Rapid Autonomy Integration Lab (RAIL) for developing new capabilities [75].…”
Section: Enhanced Intelligence and Autonomymentioning
confidence: 99%
“…The concepts of automation and intelligent manufacturing have emerged as the driving force behind industrial development in the modern era [1]. As technological advancements lead to increasingly complex machinery and equipment being used on production lines, there is a growing demand for precision operation and efficiency in ever-changing production environments [2].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al combined the feature extraction capability of the attention mechanism and the time-series memory capability of the Long Short-Term Neural Network (LSTM) to construct an exhaust temperature prediction model for MDE and set the fault threshold for exhaust temperature prediction based on the distribution of residuals between the model's predicted value and the actual value using a process control method [18]. Ji et al proposed a hybrid neural network prediction model based on deep learning for MDE exhaust temperature (EGT) prediction and demonstrated that the proposed CNN-BiLSTM-Attention prediction accuracy is higher by comparing experiments with other neural network prediction models [19].…”
Section: Introductionmentioning
confidence: 99%